HuR stabilizes a polyadenylated form of replication‐dependent histone mRNAs under stress conditions. Issue 2 (10th October 2018) - Ryu, Incheol; Park, Yeonkyoung; Seo, Jwa-Won; Park, Ok Hyun; Ha, Hongseok; Nam, Jin-Wu; Kim, Yoon Ki
ABSTRACT: All metazoan mRNAs have a poly(A) tail at the 3′ end with the exception of replication‐dependent histone (RDH) mRNAs, which end in a highly conserved stem‐loop (SL) structure. However, a subset of RDH mRNAs are reported to be polyadenylated under physiologic conditions. The molecular details of the biogenesis of polyadenylated RDH [poly(A) + RDH] mRNAs remain unknown. In this study, our genome‐wide analyses reveal that puromycin treatment or UVC irradiation stabilizes poly(A) + RDH mRNAs, relative to canonical RDH mRNAs, which end in an SL structure. We demonstrate that the stabilization of poly(A) + RDH mRNAs occurs in a translation‐independent manner and is regulated via human antigen R (HuR) binding to the extended 3′ UTR under stress conditions. Our data suggest that HuR regulates the expression of poly(A) + RDH mRNAs.—Ryu, I., Park, Y., Seo, J.‐W., Park, O. H., Ha, H., Nam, J.‐W., Kim, Y. K. HuR stabilizes a polyadenylated form of replication‐dependent histone mRNAs under stress conditions. FASEB J. 33, 2680–2693 (2019). www.fasebj.org